20.6k views
2 votes
An equation is shown below:

6(2x – 11) + 15 = 3x + 12

Part A: Write the steps you will use to solve the equation, and explain each step. (6 points)

Part B: What value of x makes the equation true? (4 points)

Source
StylesFormatFontSize

User B Cotter
by
5.2k points

1 Answer

6 votes

Answer:

x = 7

Explanation:

Distribute -

12x − 66 + 15 = 3x + 12

Combine Numbers and Variables -

12x - 51 = 3x +12

Get x on one side (isolate x) -

9x - 51 = 12

9x = 63

Divide 9 -

x =7

User Jacob Amos
by
4.2k points